Iman di Tengah Penderitaan: Suatu Inspirasi Teologis-Biblis Kristiani - Hidayat, Elvin Atmaja (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2016)
Suffering is a reality experienced by every human being as an integral part of their life. As part of one’s life, suffering is inevitable. Some people whose faith in the benevolent God has been shaken by their worst suffering ask the question: “Why does not God eliminate suffering if He is gracious and omnipotent?” This article sheds light on the problem of suffering using the Scriptures and theology, to find the different meanings behind it. From the biblical perspective, it will explore a number of meanings of suffering that essentially assert how suffering also serves to bring goodness to human life. These meanings are then complemented with a theological perspective which is based on the three aspects of soteriology, ecclesiology, and eschatology. Through this exploration, Christians are invited to “make peace” with their suffering by way of finding its different meanings. Suffering as a ‘gift’ might help the believers embrace life in its fullness and accept their being human. The concept of God as the ‘Loving Father’ could also help them find strength in facing suffering and grow in their faith as God’s children.